Synthesis of nanoherbal from ethanol extract of Indonesian fern selaginella plana and antibacterial activity assay - Sutoyo, Suyatno; Amaria, Amaria; Sanjaya, Gusti M.; Hidayah, Rusly; Sari, Devy P; Dwitarani, Nabella; Oktavia, Farida D.; Ahmad Fadzillah, Nurrulhidayah (2022)
Selaginella plana is one of the ferns that grows widely in Indonesia and has been used by the people as food, ornamental plants and traditional medicine. The preparation of S. plana extract in the form of nanoparticles can overcome the weakness of the extract, namely the low water solubility, bioavailability, stability, and absorption so as to increase its efficacy as a herbal medicine. Research related to the synthesis of nanoherbal from Selaginella plana as an antibacterial had never been reported. This study aims to synthesize nanoherbal from the ethanol extract of S. plana and test for its antibacterial activity. Extraction was carried out by maceration method, synthesis of nanoherbal by ionic gelation method, and antibacterial assay by disc diffusion method. The synthesized nanoherbal were characterized by FT-IR spectrophotometer, zetasizer nano, and scanning electron microscopy (SEM). The results showed that nanoherb of formula-1 (F-1) had a particle size in nanoparticle range (701.5467.72 nm) and had a zeta potential of +499.378.00 mV. The shift on the stretching vibration of the O-H group (3370.12 cm -1 ), the bending vibration of the N-H (1563.55 cm-1 ), and the appearance of the vibration of the phosphate group (1083.86 cm-1 ) supported the formation of nanoherbal in F-1. The F-1 nanoherbal has very strong antibacterial activity against E. coli, S. dysentriae, and S. aureus as well as strong antibacterial activity against B. subtilis. It showed stronger antibacterial activity than the ethanol extract of Selaginella plana. Thus the F-1 nanoherbal has the potential to be developed as an antibacterial agent